International Legal Challenges for the Twenty-first Century : joint conference of the Australian & New Zealand Society of International Law and the American Society of International Law. - International Legal Challenges for the Twenty-first Century, (2000 : Sydney, N.S.W. and Canberra, A.C.T.); American Society of International Law.; Australian and New Zealand Society of International Law.; Australian National University. Centre for International and Public Law. (Canberra : Centre for International and Public Law, Faculty of Law, Australian National University, 2000)
International Legal Challenges for the Twenty-first Century: Joint Conference of the Australian and New Zealand Society of International Law and the American Society of
Includes bibliographical references.
Keywords: International law -- Congresses